Drug used in controlling chickens diseases, the withdrawal periods, and the threats of drugs residues in food chain. A review - Kelvin Ngongolo; Kitojo Omary; Chota Andrew (The East Java Biological Society, 2020)
Drugs have been used by many farmers for the treatment of most infectious diseases in chicken regardless of their residue effects to human health if proper management has not adhered. This paper focuses on finding out the common chicken diseases, their prevalence, drugs used for treatment, and their residue implication in the chicken products and by-products. A systematic literature-review was used to synthesis the information from soft and hard copy sources of information. In this paper, it was noted that different infectious diseases were affecting chicken in Tanzania and other countries including Newcastle (Prevalence 7-90% per flock), Infectious bursal disease (Prevalence 7-100% per flock), Fowl Cholera (Prevalence 1-60% per flock), and Fowl Typhoid (Prevalence 0-20% per flock). As a remedy, drugs such as Amprolium, oxytetracycline, and sulphanilamide were used for treatment which could prompt antibiotic residues in chicken products and by-products. The antibiotic residue was reported in meat, eggs, liver, and kidneys of the chicken which are considered edible to a human thus posing public health challenges. In this regard, there is a need to create awareness to the farmers on the proper use of the drugs. In this case, the understanding of the withdrawal period for the applied drugs can minimize the risk of drug residues in chicken products